Uruguay - Stads, Gert-Jan; Cotro, Beatriz; Allegri, Mario (International Food Policy Research Institute, 2008)
Quantitative data are important in measuring, monitoring, and benchmarking the inputs, outputs, and performance of agricultural science and technology (S&T) systems. They are an indispensable tool when it comes to assessing the contribution of agricultural S&T to agricultural growth and, more generally, to economic growth. S&T indicators assist research managers and policymakers in policy formulation of and decision making about strategic planning, priority setting, monitoring, and evaluation. They also provide information to government and other institutions (e.g., policy research institutes, universities, and the private sector) involved in the public debate on the state of agricultural S&T at the national, regional, and international levels. This country brief reviews the major investment, capacity, and institutional trends in public agricultural research in Uruguay since 1981, using data recently collected under the Agricultural Science and Technology Indicators (ASTI) initiative (IFPRI 2007–08).1 It provides important updates on trends in Uruguay’s public agricultural research previously published by Beintema et al. (2000).